Paediatric Spectacle Prescription - Wangchuk Doma; Abhishek Dagar (Delhi Journal of Ophthalmology)
The prescription of spectacles in children depends on the individual need of the child and other associated factors like strabismus and amblyopia. Several guidelines have been published to help ophthalmologists when prescribing optical correction in infants and children, including the publication by the American Academy of Ophthalmology. The purpose of this paper is to reassess and review the guidelines to assist the clinician in deciding when to prescribe spectacles in children, and the amount of refractive error which should be corrected, with a view to fulfilling the particular clinical requirements of each child.